Gymnasium Reports as a Source of Ukrainian Schooling History in Eastern Galicia During the Interwar Period - Zanik, Halyna (Pedagogical Discourse, 2013)
Reports of gymnasiums with teaching in the Ukrainian language in Eastern Galicia, which were used during the interwar period are examined in the article. National and educational traditions of Ukrainian secondary schools are considered. Some aspects of organizing and conducting educational work under alien domination are analysed. Special attention is paid to the characteristics of the hobby group work. Author identifies the factors that led to changes in the educational plans of schools in Eastern Galicia in the Second Polish Republic in the interwar period.